STRATEGY FOR INCREASING STATE REVENUE NOT TAX AT SAMUDERA BUNGUS FISHERY - Wagimin Wagimin; Lamun Bathara; Tince Sofyani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research is an analysis of efforts to increase the Non-Tax State Revenue (PNBP) of fishing ports by the Bungus Ocean Fishing Port. This research was conducted in February 2020. This research was conducted with a case study approach based on the results of observations and analysis at PPS Bungus. The data collected consisted of primary and secondary data. Data analysis using the SWOT method. The data was collected using , interviews and field observations. From the analysis, several strategies were identified to increase PNBP, namely: (a) Tuna center areas and sufficient potential for SDI Tuna to make PPS a base for fishing fleets. (b) ISO 9001; 2008 certification can simplify the process of utilizing land available to investors. (c) improve ship services in accordance with ISO 9001; 2008 standards. (d) Improving facilities and infrastructure will provide additional PNBP from various fields. (e) Conducting various forms of promotion related to various facilities and advantages of investing in the port will make PPS Bungus a port that is attractive to investors. The implication of the results of this study is the need for proper repair, management and utilization of facilities and facilities that are included in the list of key strategies. (d) Improved facilities and infrastructure will provide additional PNBP from various fields. (e) Conducting various forms of promotion related to various facilities and advantages of investing in the port will make PPS Bungus a port that is attractive to investors. The implication of the results of this study is the need for proper repair, management and utilization of facilities and facilities that are included in the list of key strategies. (d) Improved facilities and infrastructure will provide additional PNBP from various fields. (e) Conducting various forms of promotion related to various facilities and advantages of investing in the port will make PPS Bungus a port that is attractive to investors. The implication of the results of this study is the need for proper repair, management and utilization of facilities and facilities that are included in the list of key strategiesKey words: non-tax state revenue, fishing port. PPS Bungus, SWOT